Analisis Perhitungan Harga Pokok Produksi pada UMKM Haruma Kerupuk Simbaw Waringin Lampung Tengah - Asti Sayidatina Fedurinam; Fatma Eldayena; Mia Ay Putri; Nazila Aolivia Hindana; Yunita Zahra; Esti Apridasari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The calculation and estimation of production costs are greatly influenced by the application of appropriate methods, ensuring that the resulting production costs reflect the actual value. This research was conducted on micro, small, and medium enterprises (MSMEs) in Simbar Waringin, specifically cracker processing businesses. The purpose of this study was to analyze the production cost calculations and cost allocations applied by MSMEs in Simbar Waringin using the full costing method. The data used in this study were qualitative data presented descriptively, and quantitative data presented numerically. Data sources were obtained from primary data through interviews with cracker business owners in Simbar Waringin, and secondary data were obtained from a literature review and other supporting literature. The results of the study indicate that obtaining production costs using the full costing method is superior in analyzing production costs because it includes all overhead costs, both fixed and variable, during the production process.